Impact of nutrition education programs on complementary feeding: a comparative study among Nigerian men and women - Oyeneye, Halimat O. (International Journal Of Community Medicine And Public Health, 2024)
Background: The study assessed how nutrition education programs impact complementary feeding behaviours, with a particular emphasis on understanding the experiences of both men and women in Nigeria. Methods: The study design employed a mixed-methods approach, including a qualitative and quantitative approach, and included 1167 women and 571 men in various places in the north, south, west, and eastern parts of Nigeria. A pre-tested, semi-structured questionnaire about supplemental feeding that was given by interviewers was used to gather the data. Results: The study reveals that most mothers are between the ages of 20 and 40, with a majority of them having completed primary and secondary school. The majority of respondents belong to the medium class, with 42.7% starting their children on cereal too soon at six months. 82.4% supplement their infant's diet with fortified pap, primarily made with infant formula. The majority of mothers use various feeding methods, with 57.1 percent using cups, plates, and spoons, 8.1% using hand feeding, and 8.4% using bottle feeding. Only 5.7% clean their hands after feeding and sanitize their food utensils. The study also shows that traditional gender norms, where men are primarily breadwinners, are being challenged by more progressive views, with 21.2% believing in equal sharing of caregiving responsibilities. Conclusions: The study reveals that Nigeria's supplemental feeding practices are insufficient because of early intake, inadequate follow-up, the prevalence of costly commercial formula and local cereal gruels for meals, and a shift toward shared caregiving responsibilities.